Status on Phytoremediation of Heavy Metals in India- A Review - Mandal, A.; Purakayastha, T. J.; Ramana, S.; Neenu, S.; Bhaduri, Debarati; Chakraborty, K.; Manna, M. C.; Rao, A. Subba (International Journal of Bio-resource and Stress Management, 2014)
Since the dawn of the industrial revolution, mankind has been introducing numerous hazardous compounds into the environment at an exponential rate. These hazardous pollutants consist of a variety of organic compounds and heavy metals (Cu, Pb, Cd, Ni, Fe, Mn, and Zn), which increasingly pose serious risks to human health. Heavy metal contamination is of special concern due to widespread reports emanating both from India and abroad about various diseases and disorders observed both in human and livestocks due to metal toxicity. The pollution of environment particularly from hazardous heavy metals is also considered as a vital societal problem. Thus, understanding the existing heavy metal pollution in India required a special attention for remediation through eco-friendly approach by using plants called phyto-remediation. In this review, we have highlighted the major research outcomes by Indian researchers working in the area of technologies like phytoextraction, phytoaccumulation, rhizofiltration and phytostabilization. Finding the suitable hyperaccumultor plant species is of first and foremost step for successful application of this economic and useful technology. This review attempts to address the major works done in India and will give readers a vivid idea of scope of phytoremediation with its possible benefits on agriculture. This technique hold a great promise for decontamination of heavy metals from soil and water bodies with successful intervention of interdisciplinary researchers, but challenges remain before commercialization and field scale application. Phytoremediation, a new-generation technology for both agricultural and environmental sustainability also widens up many new areas of researches for generations to come.